Association between mortality and critical events within 48 hours of transfer to the pediatric intensive care unit - Liang, Huan; Carey, Kyle A.; Jani, Priti; Gilbert, Emily R.; Afshar, Majid; Sanchez-Pinto, L. Nelson; Churpek, Matthew M.; Mayampurath, Anoop (Frontiers in Pediatrics, 2023)
Introduction: Critical deterioration in hospitalized children, defined as ward to pediatric intensive care unit (PICU) transfer followed by mechanical ventilation (MV) or vasoactive infusion (VI) within 12 hours, has been used as a primary metric to evaluate the effectiveness of clinical interventions or quality improvement initiatives. We explore the association between critical events (CEs), i.e., MV or VI events, within the first 48 hours of PICU transfer from the ward or emergency department (ED) and in-hospital mortality. Methods: We conducted a retrospective study of a cohort of PICU transfers from the ward or the ED at two tertiary-care academic hospitals. We determined the association between mortality and occurrence of CEs within 48 hours of PICU transfer after adjusting for age, gender, hospital, and prior comorbidities. Results: Experiencing a CE within 48 hours of PICU transfer was associated with an increased risk of mortality (OR 12.40 [95% CI: 8.12-19.23, P <0.05]). The increased risk of mortality was highest in the first 12 hours P<0.05]) but persisted in the 12-48 hour time interval P<0.05]). Varying levels of risk were observed when considering ED or ward transfers only, when considering different age groups, and when considering individual 12-hour time intervals. Discussion: We demonstrate that occurrence of a CE within 48 hours of PICU transfer was associated with mortality after adjusting for confounders. Studies focusing on the impact of quality improvement efforts may benefit from using CEs within 48 hours of PICU transfer as an additional evaluation metric, provided these events could have been influenced by the initiative.